The Profitability of Momentum Investment Strategy in an International Stock Market Setting - Kuuppelomäki, Niina (My University, 2016)
This Master’s thesis examines the profitability of four different momentum investment strategies with formation periods of 3–12 months and each predicting the returns 2 months ahead during the years from 2006 to 2015 in an international stock market setting. Stocks of 11 different indices (CAC 40, DAX, FTSE 100 Index, MICEX, Nikkei 225, OMX Helsinki 25, OMX Stockholm 30, ASX 100, TSX 60, S&P 100 and EUROSTOXX 50) which represent four different continents are used in order to determine whether or not momentum gains exist. This thesis adopts the view of an American investor who is investing in a global pool of stocks. In total 705 stocks are used in the analysis and three different portfolios are formed from these stocks. Out of these portfolios the winner portfolio is bought and the loser portfolio is sold. This analysis is repeated four times for different datasets. Two datasets include stocks and two datasets include the used indices as a whole. The represented countries are also analyzed individually in order to point out the differences between countries. The results of the analysis for the whole time period indicate that the momentum returns are still present and persistent even though the stock market anomaly i.e. the used investment strategy has been found decades earlier. The momentum returns are also statistically significant in many of the used strategies. The results for the crisis period suggest that the momentum strategy is either not profitable or not statistically significant during a time period with a financial crisis. The results for the time period after the crisis however suggest that the momentum has been again profitable but the magnitude of the returns is smaller than during the whole time period. The results for the countries alone, however, point out that many of the countries do not have statistically significant momentum returns when the country is analyzed alone. Only U.S. and Great Britain have significant returns for all of the strategies. Even though these results are not statistically significant in all aspects, they still provide evidence for a well-researched finance topic and point out the importance of momentum in an academic and current setting.
Keywords: Momentum; international; global; stocks; indices; profitability; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|